2016
DOI: 10.1126/science.aac4951
|View full text |Cite
|
Sign up to set email alerts
|

Taking race out of human genetics

Abstract: Engaging a century-long debate about the role of race in science

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
361
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 527 publications
(365 citation statements)
references
References 14 publications
3
361
0
1
Order By: Relevance
“…Race is a societal construct that is often an inadequate proxy for a study participant's genetics. [20][21][22] While diverse research cohorts have elucidated differences in human leukocyte antigen-typing that mediate Stevens-Johnson syndrome, 23 genetic variation in response to antiretroviral medication, 24 and variability in prevalence of drugtargeted tumor markers, 25 these findings were ultimately based on the genetic diversity of a racially and ethnically diverse study cohort. Racial and perhaps to a greater extent, ethnic diversity in research will continue to be critical for ensuring all individuals have access to new treatment.…”
Section: Figure 1 Systematic Review Methods Section Flowchartmentioning
confidence: 99%
“…Race is a societal construct that is often an inadequate proxy for a study participant's genetics. [20][21][22] While diverse research cohorts have elucidated differences in human leukocyte antigen-typing that mediate Stevens-Johnson syndrome, 23 genetic variation in response to antiretroviral medication, 24 and variability in prevalence of drugtargeted tumor markers, 25 these findings were ultimately based on the genetic diversity of a racially and ethnically diverse study cohort. Racial and perhaps to a greater extent, ethnic diversity in research will continue to be critical for ensuring all individuals have access to new treatment.…”
Section: Figure 1 Systematic Review Methods Section Flowchartmentioning
confidence: 99%
“…2014; Yudell et al. 2016). It has been suggested that human genetic diversity follows in part from different selection pressures of divergent geographies and social structures (Wade 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Racial inferiority [is] a part of the ether of Western society.” With this history in mind, we were cautious about studying a genetic variant that makes those of African ancestry more likely to develop kidney disease than Whites. Some scientists have suggested that racial terminology be phased out of genetics, 12 because racial/ethnic categories are social constructs, which may complicate and potentially confound research while engaging a long and problematic history of race-based and eugenics research. Although the board also views race as a social construct, we recognize that ancestry has biological/genetic components that may—as in the case of APOL1—significantly impact an individual’s susceptibility to certain diseases.…”
Section: Methodsmentioning
confidence: 99%